Halal market opportunities through research findings / Sharifah Zannierah Syed Marzuki ... [et al.] - Syed Marzuki, Sharifah Zannierah; Zainal Abidin, Zanariah; Kamall Khan, Yasmin; Osman, Che Asniza; Ling, Oliver Hoon Leh (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2018)
Halal market has becoming a phenomenal reality globally with the growing number of customers that encompass Muslims and non-Muslims. The emergence of a global halal market has opened vast opportunities for firms in numerous industries that include food, fashion, hospitality, agriculture and services. It is gathered from the literature that notable factors contribute to the upward potential of halal industry. New dimensions of halal areas are expected to be explored by the halal market players to develop more innovative halal offerings thus benefit all consumer groups. Realizing that market intelligence is important, the advances of robotics, Internet of Things, Big Data are ways to assist and support the halal eco-system thus further operationalise halal requirements outlined by the Quran (the Holy Book of Islam) and Hadith (practices and sayings of the Prophet of Muhammad, peace be upon Him). Common issues pertaining to halal matters are seen as challenges for firms to act on proactively and be prepared with effective plans and strategies as the consumers for halal products and services come from wide range of race and religion worldwide. Market players and exporters need to serve a Muslim community of varied Islamic school of thoughts that appear to be very challenging in different countries. It is interesting to explore the halal market opportunities in halal literature that makes it so significant for this high demand market.